The application of biomaterials in osteogenesis: A bibliometric and visualized analysis - Wang, Jie; Chi, Yuan; Yang, Baohui; Zhang, Qiongchi; Wang, Dong; He, Xijing; Li, Haopeng (Frontiers in Bioengineering and Biotechnology, 2022)
Osteogenesis serves an important role in bone tissue repairing. Novel biomaterials are widely prevalent as materials for orthopedic implants due to their biocompatibility and osteogenetic ability. The purpose of this study was to comprehensively analyze hotspots and future trend of biomaterials research in osteogenesis based on bibliometric and visualized analysis. A total of 1523 papers about biomaterials research in osteogenesis between 2000 and 2021 were included in this study. During the above 20 years, China's leading position in the global biomaterials research in osteogenesis was obvious, and it was also the country that most frequently participates in international cooperation. Chinese Academy of Sciences was the most productive institution and the leader of research cooperation. Acta Biomaterialia and Biomaterials have published the largest number of articles in the field of biomaterials research in osteogenesis. Meanwhile, Acta Biomaterialia and Biomaterials were also the two journals with the highest total citation frequency. Wu CT, Chang J, Kaplan DL, and Xiao Y all made important contributions in the field of biomaterials research in osteogenesis. At present, there are five research hotspots in the field of biomaterials research in osteogenesis: (1) the immunomodulatory role of biomaterial-related inflammatory; (2) mechanisms of osteogenesis in biomaterials; (3) 3D printing and clinical application of biomaterials; (4) bone tissue engineering for biomaterial osteogenesis; and (5) regenerative medicine for biomaterial osteogenesis. The results of this study showed that mechanisms of osteogenesis in biomaterials, bone tissue engineering for biomaterial osteogenesis, and regenerative medicine for biomaterial osteogenesis will remain research hotspots in the future. International cooperation was also expected to expand and deepen the field of biomaterials research in osteogenesis.